Innovative Learning in Teaching Listening Comprehension - Mery Silalahi (LPPM Politeknik Pratama, 2023)
The concept of innovation is about something new; something different from what was practiced in teaching English all this time. Listening is one of the competencies that must be possessed in learning English. Along with the development of the times, teaching methods also developed. Educators are required to be able to develop teaching methods that can adjust to what is needed for this age, including in an effort to improve students' listening comprehension in learning English. Most of children have problems in listening. One of the listening’s problems is comprehension the speed of delivery is beyond the control of listeners. Besides, it is not always possible for learners to have words repeated. This is a main problem in learning situations. The small size of the learner vocabulary frequently impedes listening comprehension. The speaker does not always use words the listener knows. Sometimes when listeners encounter a new word, they stop to figure out the meaning of that word, and they therefore, miss the next part of the speech. Listeners may not recognize the signals that the speaker is using to move from one point to another especially if the learner is listening to a radio where he cannot see the facial expressions of the speaker. It can also be very challenging for listeners to concentrate in a foreign language. From this reason, educators should have an innovative way to overcome the problem. Students rarely listen to anything without an expectation of what’s coming next. So the innovative way to solve those problems is students need a bit of preparation before they get stuck into a listening task and they need a reason to listen. If the students have Internet access teacher can set longer listening tasks as homework. They can listen to extracts of 20 minutes or so in preparation for a class discussion the following lesson. Although students do sometimes become anxious when they hear the unfamiliar, texts downloaded from the Internet are easy for the students to access by themselves for personal study at another time.